Managing straw and nitrogen fertilizer based on nitrate threshold for balancing nitrogen requirement of maize and nitrate residue. (1st March 2023) - Guo, Ru; Qian, Rui; Han, Fei; Khaliq, Abdul; Hussain, Sadam; Yang, Ling; Zhang, Peng; Chen, Xiaoli; Ren, Xiaolong
Abstract: Optimized straw and nitrogen (N) fertilizer management instrumental in realizing synchronized soil N supply and crop N requirement (Nr), reducing nitrate-N leaching and achieving efficient and cleaner agricultural production systems, especially in the areas with poor soil fertility retention. A three-year field trial during 2019–2021 was conducted in northwest China with different straw incorporation methods (SM) (without straw or biochar (NI), straw incorporation (SI) and straw-derived biochar incorporation (BI)) combined with four N application rates (NR) (0, 225, 300, and 375 kg ha −1 ). The grain yield, Nr and the critical nitrate threshold in the root zone (0–100 cm soil layer; NAc) after maize harvest were determined to optimize straw and N inputs for maize yield enhancement and nitrate residue control. Then the prediction methods of optimal N rate determined with NAc (TONR) and soil testing were modified for straw or straw-derived biochar incorporated spring maize production in the future. The results showed that grain yield and nitrate residue in the deep soil (100–200 cm soil; NA100-200 ) after maize harvest increased by N application, grain yield further increased but NA100-200 decreased when combined with SI and BI ( P  < 0.05). In particular, a significant increase in grain yield, Nr and N recovery efficiency (NRE) under BI was attributed to an increase in soil N supply and N assimilation after the tassel stage (VT) of maize as compared with SI ( P  < 0.05). The NAc values were determined as 49, 104 and 67 kg ha −1 under NI, SI and BI, respectively for maintaining N supply and preventing leaching into 100–200 cm soil. Compared with the economically optimal N rate (EONR), BI combined with TONR (268 kg N ha −1 ) reduced the N rate by 22 kg ha −1 per year and NA100-200 by 5.3% and increased NRE by 5.7% to achieve 99.7% maximum yield (14.448 Mg ha −1 ), which was a sustainable management method of straw and N rate for enhancing spring maize production and controlling soil nitrate leaching. Graphical abstract: Image 1 Highlights: Biochar incorporation increased grain yield, N uptake and NRE than straw. Straw more effective than biochar in preventing nitrate leaching into deep soil. Straw or biochar incorporation improved nitrate threshold in 0–100 cm soil layer. Modified the N management methods proposed under straw or biochar incorporation. Biochar combined with optimized N rate could achieve sustainable agriculture.